Manajemen Pembelajaran Bahasa Berbasis Integrasi-Interkoneksi Menuju World Class University - Tulus Musthofa; Agung Setiyawan; M. Ja’far Sodiq (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
Maulana Malik Ibrahim State Islamic University Malang is is known as a succesfull campusin running foreign languages learning, especially Arabic. This research aimed to compare the management of Arabic language learningin UIN Maliki and UIN Sunan Kalijaga to generate some feed backs in improving the quality of language learning as wellas an effort towards world class university. The result of research showed the advantages of each university in running arabic learning. UIN Maliki Malang focuses on optimizing arabic learning in dormitory (ma’had) with a variety of language activities, while UIN Sunan Kalijaga Yogyakarta focuses on integrating scientific material and arabic language.